Characterization of Air-Based Photovoltaic Thermal Panels with Bifacial Solar Cells - P. Ooshaksaraei; K. Sopian; R. Zulkifli; Saleem H. Zaidi (International Journal of Photoenergy)
Photovoltaic (PV) panels account for a majority of the cost of photovoltaic thermal (PVT) panels. Bifacial silicon solar panels are attractive for PVT panels because of their potential to enhance electrical power generation from the same silicon wafer compared with conventional monofacial solar panels. This paper examines the performance of air-based bifacial PVT panels with regard to the first and second laws of thermodynamics. Four air-based bifacial PVT panels were designed. The maximum efficiencies of 45% to 63% were observed for the double-path-parallel bifacial PVT panel based on the first law of thermodynamics. Single-path bifacial PVT panel represents the highest exergy efficiency (10%). Double-path-parallel bifacial PVT panel is the second preferred design as it generates up to 20% additional total energy compared with the single-path panel. However, the daily average exergy efficiency of a double-path-parallel panel is 0.35% lower than that of a single-path panel.